1996
DOI: 10.2307/3870319
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis: A Functional Paradigm for Programmed Plant Cell Death Induced by a Host-Selective Phytotoxin and Invoked during Development

Abstract: The host-selective AAL toxins secreted by Alternaria alternata f sp lycopersici are primary chemical determinants in the Alternaria stem canker disease of tomato. The AAL toxins are members of a new class of sphinganine analog mycotoxins that cause cell death in both animals and plants. Here, we report detection of stereotypic hallmarks of apoptosis during cell death induced by these toxins in tomato. DNA ladders were observed during cell death in toxin-treated tomato protoplasts and leaflets. The intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 0 publications
3
127
0
2
Order By: Relevance
“…Lesion size was reported to be slightly larger in the transgenic plants (37), although the overall role of these transgenes with respect to plant disease remained an open question. Previous studies showed that tomato protoplasts treated with the mycotoxin fumonisin B1 underwent PCD-like response as indicated by DNA ladders and terminal deoxynucleotidyltransferasemediated UTP end labeling-positive reacting cells (11). Recently, Ausubel and colleagues (38,39) have shown that fumonisin B1 treatment of Arabidopsis protoplasts results in terminal deoxynucleotidyltransferase-mediated UTP end labelingpositive reacting cells and also that toxin infiltration of intact plants resulted in cell death, generation of reactive oxygen intermediates, and other biochemical markers associated with plant defense responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion size was reported to be slightly larger in the transgenic plants (37), although the overall role of these transgenes with respect to plant disease remained an open question. Previous studies showed that tomato protoplasts treated with the mycotoxin fumonisin B1 underwent PCD-like response as indicated by DNA ladders and terminal deoxynucleotidyltransferasemediated UTP end labeling-positive reacting cells (11). Recently, Ausubel and colleagues (38,39) have shown that fumonisin B1 treatment of Arabidopsis protoplasts results in terminal deoxynucleotidyltransferase-mediated UTP end labelingpositive reacting cells and also that toxin infiltration of intact plants resulted in cell death, generation of reactive oxygen intermediates, and other biochemical markers associated with plant defense responses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar indicators of PCD can appear in the diseased state (susceptible or compatible reaction). For example, in plants that are sensitive to toxin-producing fungi, e.g., Fusarium moniliforme, Alternaria alternata, and Cochliobolus victoriae, certain features of apoptosis are observed (11,12). In addition, cucumber mosaic virus D satellite RNA has been shown to induce morphological features of PCD in infected tomato (13).…”
mentioning
confidence: 99%
“…Furthermore, cell death in response to pathogen attack, and in response to a variety of abiotic factors such as ozone and UV radiation also fall within the definition of PCD. A number of morphological similarities were found between animal cells undergoing apoptosis and dying plant cells, including compaction and shrinkage of the cytoplasm and nucleus, DNA and nuclear fragmentation, and the formation of DNA-containing (apoptotic-like) bodies (Wang et al, 1996;De Jong et al, 2000). Although such typical apoptotic hallmarks have not been established in all the cases of plant PCD, the observations do suggest the existence of an apoptotic machinery in plant cells.…”
Section: Pcd and Apoptosismentioning
confidence: 75%
“…Several apoptogenic effectors, such as caspases (cysteine proteases) [9][10][11][12], CAD/DFF40 (caspase-activated DNase/40 kDa DNA fragmentation factor) [9][10][11][12], endoG (mitochondrial endonuclease G) [13], DNase I [14], DNase II [15], AIF (apoptosis-inducing factor) [16] and Acinus (apoptosis chromatin condensation inducer in the nucleus) [17], have been implicated in mediating these nuclear disintegration processes using a cell-free system. In plants, chromatin condensation and DNA laddering are induced during PCD in response to biotic/abiotic stresses and developmental factors [4,6,[18][19][20][21][22]. However, only limited information is available about plant effectors, especially those involved in the executive phase of plant PCD.…”
Section: Introductionmentioning
confidence: 99%
“…The defense reaction often includes the rapid and localized collapse of the challenged cells, known as the hypersensitive response (HR) [1]. The HR displays several biochemical and morphological features of animal apoptosis [2][3][4][5][6], which is a process of programmed cell death (PCD) essential in development, tissue homeostasis and response to environmental stresses [7].…”
Section: Introductionmentioning
confidence: 99%